Influence of ceramide on lipid domain stability studied with small-angle neutron scattering: The role of acyl chain length and unsaturation. (July 2022) - DiPasquale, Mitchell; Deering, Tye G.; Desai, Dhimant; Sharma, Arun K.; Amin, Shantu; Fox, Todd E.; Kester, Mark; Katsaras, John; Marquardt, Drew; Heberle, Frederick A.
Abstract: Ceramides and diacylglycerols are groups of lipids capable of nucleating and stabilizing ordered lipid domains, structures that have been implicated in a range of biological processes. Previous studies have used fluorescence reporter molecules to explore the influence of ceramide acyl chain structure on sphingolipid-rich ordered phases. Here, we use small-angle neutron scattering (SANS) to examine the ability of ceramides and diacylglycerols to promote lipid domain formation in the well-characterized domain-forming mixture DPPC/DOPC/cholesterol. SANS is a powerful, probe-free technique for interrogating membrane heterogeneity, as it is differentially sensitive to hydrogen's stable isotopes protium and deuterium. Specifically, neutron contrast is generated through selective deuteration of lipid species, thus enabling the detection of nanoscopic domains enriched in deuterated saturated lipids dispersed in a matrix of protiated unsaturated lipids. Using large unilamellar vesicles, we found that upon replacing 10 mol% DPPC with either C16:0 or C18:0 ceramide, or 16:0 diacylglycerol (dag), lipid domains persisted to higher temperatures. However, when DPPC was replaced with short chain (C6:0 or C12:0) or very long chain (C24:0) ceramides, or ceramides with unsaturated acyl chains of any length (C6:1(3), C6:1(5), C18:1, and C24:1), as well as C18:1-dag, lipid domains were destabilized, melting at lower temperatures than those in the DPPC/DOPC/cholesterol system. These results show how ceramide acyl chain length and unsaturation influence lipid domains and have implications for how cell membranes might modify their function through the generation of different ceramide species. Highlights: Chain-length matching ceramides and diacylglycerols stabilize domains. Short chain ceramides, very long chain ceramides, or ceramides with unsaturated acyl chains destabilize domains. Small-angle neutron scattering methods reveal the influence of ceramide structure on domain stability.